A newly thermoactive and detergent‐stable lipase from annular sea bream (Diplodus annularis): Biochemical properties. (5th November 2015) - Smichi, Nabil; Miled, Nabil; Gargouri, Youssef; Fendri, Ahmed
Abstract: A lipolytic activity was located in the annular seabream pyloric caeca, from which a digestive lipase (AsDL) was purified. Pure AsDL has an apparent molecular mass of 50 kDa. The purified lipase is thermoactive as it displays its maximal activity on short‐ and long‐chain triacylglycerols at a temperature of 50 °C. The enzyme is alkaline resistant as it retains 90% of its maximal activity when incubated during 1 H at pH 10. No colipase was detected in the annular seabream pyloric caeca. Similar results were reported for the sardine and the gray mullet digestive systems. This is in line with the idea that colipase might have evolved in mammal animals simultaneously with the appearance of an exocrine pancreas. AsDL is a serine enzyme, like all known lipases from different origins. Interestingly, the pure lipase was found to be insensitive to Triton X‐100, a synthetic detergent, addition even at a concentration as high as 12 mM. The purified enzyme has potential applications in detergent and food industry because of its thermal activity and alkaline nature.